JoJo's bizarre adventure. Part 4, Diamond is unbreakable. 6 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2020)
"A multigenerational tale of the heroic Joestar family and their never-ending battle against evil! In April 1999, Jotaro Kujo travels to a town in Japan called Morioh to find a young man named Josuke Higashikata, the secret love child of his grandfather, Joseph Joestar. Upon finding him, Jotaro is surprised to learn that Josuke also possesses a Stand. After their strange meeting, the pair team up to investigate the town's proliferation of unusual Stands!"--Provided by publisher.